Device simulation of perovskite solar cells with molybdenum disulfide as active buffer layer - Ainon Shakila Shamsuddin; Puteri Nor Aznie Fahsyar; Norashikin Ahmad Ludin; Ibrahim Burhan; Salina Mohamad (Institute of Advanced Engineering and Science, 2019)
Organo-halide Perovskite Solar Cells (PSC) have been reported to achieve remarkably high power conversion efficiency (PCE). A thorough understanding of the role of each component in solar cells and their effect as a whole is still required for further improvement in PCE. In this paper, the effect of Molybdenum Disulfide (MoS2) in PSC with mesoporous structure configuration was analyzed using Solar Cell Capacitance Simulator (SCAPS). With the MoS2 layer which having two-fold function, acting as a protective layer, by preventing the formation of shunt contacts between perovskite and Au electrode, and as a hole transport material (HTM) from the perovskite to the Spiro-OMETAD. As simulated, PSC demonstrates a PCE, ŋ of 13.1%, along with stability compared to typical structure of PSC without MoS2 (Δ ŋ/ŋ=-9% vs. Δ ŋ/ŋ=-6%). The results pave the way towards the implementation of MoS2 as a material able to boost shelf life which very useful for new material choice and optimization of HTMs.